Synthesis and Properties of a Reinforcing Dust-Cementing Material for Thin Spray-On Liners in Mine Roadways - Gang Zhou; Shuailong Li; Yunlong Ma; Jianfei Ding; Mingguang Zhang (Advances in Materials Science and Engineering)
The sprayed concrete in mine roadways suffers from a prolonged exposure to the harsh environment in the underground mine, leading to its detachment which may compromise its supporting strength. Besides, the dust-cementing effect of the conventional concrete is poor, providing very limited contribution to suppress the dust-laden airflow. As such, the present experiment uses sodium carboxymethyl cellulose as the base to produce a novel thin spray material through graft copolymerization based on acrylic acid and polyaluminum chloride. This new material can not only reinforce the surrounding rock of the roadway but also cement the dust in the airflow. Infrared spectroscopy, X-ray diffraction, thermal gravimetric analysis, and SEM are employed collectively to study the microscale reaction and structure of the product. A suite of experiment testing is carried out concerning the performance of the developed spray material, which reveals the supreme mechanical strength and desired properties of the hardened film developed from the spray material.